Modern trends in consumer behavior of young people in the digital age (The Journal of Psychology and Sociology, 2021)
Article analyzes the current patterns of consumer behavior of today’s youth and their changes in the contest of social technologies development and network interaction. The relevance of this problem is due to the fact that in the modern world, social media has become one of the important factors influenc- ing the formation of consumer behavior and style in particular of young people. Instagram Facebook, Tiktok, VK and other platforms are used by young people as an active user of social networks, and their consumption style is being modified and implemented through such platforms. This trend is due to the fact that almost every manufacturer has its own page in social networks and presents its product. Also, famous brands, especially in the field of clothing and cosmetics, attract celebrities in order to promote their products, creating new and bright images that attract customers. The article presents an analysis of secondary data on the research topic conducted by Ola H., Rima B., Mustakas E., Jonida K. and other sociologists and researchers. The authors pay special attention to the study of changes in the style of consumption by young people in a modern society with a developed technology of network interaction. An in-depth analysis of the scientific literature on the research topic is carried out and the typology of consumer behavior in social media is presented.Key words: consumption style, youth, consumer behavior, social media.